Fragmentos de uma vida docente: criança, resistência e educação - Janei Neto, Vitor (2022)
The thesis "Fragments of a teaching life: children, resistance and education" intends to answer the following question: How do young children resist school? For this, the author starts from real and fictional scenes from the daily life of childhood schools, in which he works or has worked as a teacher, written throughout his career, which narrate and describe situations in which children use different strategies of resistance against the school institution (protests, exodus, desertions, escapes, contestations, confrontations, subversions, humor) and establishes relations and connections with the works of authors such as: Michel Foucault, Gilles Deleuze, Felix Guattari, Fernand Deligny, René Schérer, among others. Its goal is to think about children's resistance so that it is possible to reinvent our own ways of resisting in contemporaneity.